PTU-019 Pain, perception and reality – comparison of comfort scores of south asian and white british patients undergoing bowel cancer screening colonoscopy. (22nd June 2015) - Verma, AM; Hanna, MS; Lewin, V; Robinson, B; Robinson, RJ
Abstract : Introduction: There have been several studies suggesting South Asian patients have differing pain perception to White British patients. 1 Watson et al . compared hot and cold pain perception in 20 age-matched South Asian and White British volunteers, with significantly increased heat pain scores and reduced pain threshold. 2 Recently, Al-Hashimi et al showed no significant differences in post-operative pain scores and analgesia consumption in 60 South Asian patients undergoing total abdominal hysterectomy versus 60 age-matched White British controls. 3 Sedation and analgesia administration is well regulated in colonoscopy practice and comparing comfort scores in similar aged South Asian and White British screening patients is of interest to bowel cancer screening programme (BCSP) centres in ethnically diverse areas. Method: In 2014, colonoscopy screened individuals (BCSP) in Leicester and Kettering had their self-selected ethnic origin recorded. Comfort scores of 713 patients recorded in the Exeter online database was correlated to ethnic origin data and analysed. Results: Total number of patients: 713 Difference between means: 0.26 (95% CI: 0.05–0.47) Conclusion: This analysis shows mean comfort scores are significantly lower in South Asian patients (p = <0.02). This is counter to what published literature might suggest. We reported in 2014 that South Asian patients undergoing BCSP colonoscopy have significantly lower adenoma detection rates when compared to White British patients (31.68% vs 48.09% p = <0.02). 4 Perhaps fewer adenomas requiring polypectomy lead to more straightforward colonoscopy and lower comfort scores. Whatever the explanation, this analysis shows that pain perception is complex. The interaction of patient ethnicity factors (behavioural, cultural, social and psychological) are not easily predicted and requires further study. Disclosure of interest: None Declared. References: Edwards CL, Fillingim RB, Keefe F. Race, ethnicity and pain. Pain 2001; 94: 133–137 Watson PJ, Latif RK, Rowbotham DJ. Ethnic differences in thermal pain responses: a comparison of South Asian and White British healthy males. Pain 2005;118:194–200 Al-Hashimi M, Scott S, Griffin-Teall N, Thompson J. Influence of ethnicity on the perception and treatment of early post-operative pain. Pain 2014. doi: 10.1177/2049463714559254 Verma AM, Lewin V, Chilton AP, de Caestecker J, Dixon A, Jameson J, Wurm P, Robinson RJ. Variations in adenoma detection rate and cancer detection rate in individuals from different ethnic groups undergoing bowel cancer screening colonoscopy. Gut 2014;63 (Suppl 1):A122